(untitled) (The Research of Medical Science Review, 2025)
Background: Interstitial lung diseases (ILDs) represent a diverse group of pulmonary disorders. High-resolution computed tomography (HRCT) is a cornerstone in their diagnosis and management. Objective: This study aimed to evaluate the association between HRCT patterns and final diagnoses in patients with suspected ILD at a tertiary care center. Methods: This cross-sectional study with a prospective component included 128 adult patients (17-85 years) with clinical suspicion of ILD undergoing HRCT at Arif Memorial Teaching Hospital, Lahore, over a 4-month period. Non-probability convenient sampling was used. HRCT scans were reviewed by experienced radiologists, and clinical data (demographics, symptoms, exposures) were collected. Associations between HRCT patterns (UIP, NSIP, HP, organizing pneumonia, DIP) and final diagnoses were analyzed. Short-term and long-term outcomes were also assessed. Results: The mean age of participants was 47.9 ± 14.2 years, with a slight male predominance (54.7%). Common presenting symptoms included dyspnea (94.5%) and chronic cough (91.4%). Occupational dust was the most frequently reported exposure (18.8%). Strong associations were observed between specific HRCT patterns and diagnoses: UIP with IPF (77.8%), NSIP with NSIP (75.9%), HP with HP (70.5%), organizing pneumonia pattern with organizing pneumonia (75%), and DIP pattern with DIP (66.7%). Short-term outcomes showed symptom improvement in 81.0% and PFT stabilization in 79.5% of patients. Long-term follow-up revealed an 86.7% survival rate, with 18.0% experiencing disease progression and 23.4% requiring advanced therapies. Conclusion: This study reinforces the crucial role of HRCT in suggesting specific ILD diagnoses based on characteristic patterns